Temporal Profile of Descending Cortical Modulation of Spinal Excitability: Group and Individual-Specific Effects - Xu, Jiang; Lopez, Alejandro J.; Hoque, Maruf M.; Borich, Michael R.; Kesar, Trisha M. (Frontiers in Integrative Neuroscience, 2022)
Sensorimotor control is modulated through complex interactions between descending corticomotor pathways and ascending sensory inputs. Pairing sub-threshold transcranial magnetic stimulation (TMS) with peripheral nerve stimulation (PNS) modulates the Hoffmann’s reflex (H-reflex), providing a neurophysiologic probe into the influence of descending cortical drive on spinal segmental circuits. However, individual variability in the timing and magnitude of H-reflex modulation is poorly understood. Here, we varied the inter-stimulus interval (ISI) between TMS and PNS to systematically manipulate the relative timing of convergence of descending TMS-induced volleys with respect to ascending PNS-induced afferent volleys in the spinal cord to 1) characterize effective connectivity between the primary motor cortex (M1) and spinal circuits, mediated by both direct, fastest-conducting, and indirect, slower-conducting descending pathways and 2) compare the effect of individual-specific versus standard ISIs. Unconditioned and TMS-conditioned H-reflexes (24 different ISIs ranging from -6 to 12ms) were recorded from the soleus muscle in 10 able-bodied individuals. The magnitude of H-reflex modulation at individualized ISIs (earliest facilitation delay or EFD and individual-specific peak facilitation) was compared with standard ISIs. Our results revealed a significant effect of ISI on H-reflex modulation. ISIs eliciting earliest-onset facilitation (EFD 0ms) ranged from -3 to -5ms across individuals. No difference in the magnitude of facilitation was observed at EFD 0ms versus a standardized short-interval ISI of -1.5ms. Peak facilitation occurred at longer ISIs, ranging from +3 to +11ms. The magnitude of H-reflex facilitation derived using an individual-specific peak facilitation was significantly larger than facilitation observed at a standardized longer-interval ISI of +10ms. Our results suggest that unique insights can be provided with individual-specific measures of top-down effective connectivity mediated by direct and/or fastest-conducting pathways (indicated by magnitude of facilitation observed at EFD 0ms) and other descending pathways that encompass relatively slower and/or indirect connections from M1 to spinal circuits (indicated by peak facilitation and facilitation at longer ISIs). By comprehensively characterizing the temporal profile and inter-individual variability of descending modulation of spinal reflexes, our findings provide methodological guidelines and normative reference values to inform future studies on neurophysiological correlates of the complex array of descending neural connections between M1 and spinal circuits.